VITAMIN AND MINERAL SUPPLEMENTATION FOR CHILDREN - O.V. Iozefovich (Union of pediatricians of Russia, 2011)
Vitamins and minerals play a unique role in the human health maintaining. Children's organisms are particularly sensitive to the deficiency of vitamins. Typically, the child receives all the necessary vitamins and minerals as a part of nutrition. But in a period of an intensive growth, in climatic conditions changing, increased physical and mental stress, during stress conditions or infectious diseases, as well as during the recovery period the child should receive vitamins, minerals in the mineral and vitamin complexes.Key words: vitamins, minerals, avitaminosis, hypovitaminosis, treatment, prevention, children.